2019
DOI: 10.1016/j.bbr.2018.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter (DAT) knockdown in the nucleus accumbens improves anxiety- and depression-related behaviors in adult mice

Abstract: Many epidemiological and clinical studies have demonstrated a strong comorbidity between anxiety and depression, and a number of experimental studies indicates that the dopamine transporter (DAT) is involved in the pathophysiology of anxiety and depression. However, studies using laboratory animals have yielded inconclusive results. The aim of the present study was to examine the effects of DAT manipulation on anxiety-and depression-like behaviors in mice. For this purpose, animals were stereotaxically injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 91 publications
3
24
2
1
Order By: Relevance
“…Moreover, increased DA signaling and reduced glutamatergic firing within the NAcc is associated with increased anxiety [2]. A link between reduced NAcc DAT expression and anxiolytic behavior was recently reported [41], also consistent with our findings. Given that we used an AAV9 viral serotype, Rit2-KD likely occurred across multiple DAergic circuits, including VTA PFC, VTA NAc, and SNc DS.…”
Section: Rit2 Expression Increases Throughout Postnatal Development Asupporting
confidence: 92%
“…Moreover, increased DA signaling and reduced glutamatergic firing within the NAcc is associated with increased anxiety [2]. A link between reduced NAcc DAT expression and anxiolytic behavior was recently reported [41], also consistent with our findings. Given that we used an AAV9 viral serotype, Rit2-KD likely occurred across multiple DAergic circuits, including VTA PFC, VTA NAc, and SNc DS.…”
Section: Rit2 Expression Increases Throughout Postnatal Development Asupporting
confidence: 92%
“…Using a foot-shock avoidance task, Wenzel et al (82) found that activation of VTA DA neurons enhanced active avoidance in rats, and this was blocked by D1 antagonist injection into the NAc core. In addition, knocking down the DA transporter in the NAc core, which decreases DA reuptake and increases synaptic DA levels, reduces anxiety-and depression-like behaviors (83). As depression is marked by reduced avoidance of aversive stimuli (helplessness), these data imply that dysregulation of NAc D1 receptor activation could increase vulnerability to stress-induced helplessness.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, the MIX‐by‐MAT group was generally more inactive than all the other ones at 9:00 PM. As a whole, sleep and reward disturbances (that cause major changes in circadian rhythms) can indeed result from a dysfunctional dopaminergic system (Germain & Kupfer, 2008; Nezlek et al, 1994; see Bahi & Dreyer, 2019).…”
Section: Discussionmentioning
confidence: 99%